Risk assessment of housing market segments: The lender's perspective - Mats Wilhelmsson; Jianyu Zhao (Journal of Risk and Financial Management, 2018)
It is well known that risk factors influence how investment portfolios perform from a lender's perspective; therefore, a thorough risk assessment of the housing market is vital. The aim of this paper was to analyze the risks from housing apartments in different housing market segments by using the Stockholm, Sweden, owner-occupied apartment market as a case study. By applying quantitative and systems engineering methods, we (1) established the relationship between the overall housing market and several housing market segments, (2) analyzed the results from the quantitative model, and (3) finally provided a feasible portfolio regarding risk control based on the given data. The goal was to determine how different housing segment factors could reveal risk towards the overall market and offer better outlooks for risk management when it comes to housing apartments. The results indicated that the risk could be reduced at the same time as the return increased. From a lender's perspective, this could reduce the overall risk.
Keywords: 330; mortgage portfolio; housing segments; risk assessment; hedonic modeling; analytic hierarchy process